Iraq and the knot of the geographical bracelet Adam Tooze " Polycrisis " approach as a starting point (قضايا سياسية, 2023)
This study deals with the transformations of Iraqi foreign policy in the context of a turbulent regional environment and in the context of internal transformations that push towards fundamental modifications in the directions of its foreign policy. The study also discusses Iraq's endeavors to redefine its national interests through its various soft tools, according to a vision that involves playing a regional role far from external influences and pressures, and allowing for the improvement of its relations with the surrounding countries. The study ends with a review of emerging regional challenges and their repercussions on Iraq's external orientations.